The alpha7 nicotinic acetylcholine receptor: molecular modelling, electrostatics, and energetics. - Amiri, S; Tai, K; Beckstein, O; Biggin, P; Sansom, MS (2005)
The structure of a homopentameric alpha7 nicotinic acetylcholine receptor is modelled by combining structural information from two sources: the X-ray structure of a water soluble acetylcholine binding protein from Lymnea stagnalis, and the electron microscopy derived structure of the transmembrane domain of the Torpedo nicotinic receptor. The alpha7 nicotinic receptor model is generated by simultaneously optimising: (i) chain connectivity, (ii) avoidance of stereochemically unfavourable contacts, and (iii) contact between the beta1-beta2 and M2-M3 loops that have been suggested to be involved in transmission of conformational change between the extracellular and transmembrane domains. A Gaussian network model was used to predict patterns of residue mobility in the alpha7 model. The results of these calculations suggested a flexibility gradient along the transmembrane domain, with the extracellular end of the domain more flexible that the intracellular end. Poisson-Boltzmann (PB) energy calculations and atomistic (molecular dynamics) simulations were used to estimate the free energy profile of a Na+ ion as a function of position along the axis of the pore-lining M2 helix bundle of the transmembrane domain. Both types of calculation suggested a significant energy barrier to exist in the centre of the (closed) pore, consistent with a "hydrophobic gating" model. Estimations of the PB energy profile as a function of ionic strength suggest a role of the extracellular domain in determining the cation selectivity of the alpha7 nicotinic receptor. These studies illustrate how molecular models of members of the nicotinic receptor superfamily of channels may be used to study structure-function relationships.